Karen Bray, Heather Eaton, and Whitney Bauman, eds. (2023). Earthly Things: Immanence, New Materialisms, and Planetary Thinking - LeVasseur, Todd (Journal of Posthumanism, 2024)
Containing an Introduction and twenty-two stand-alone chapters, Earthly Things is the culmination of five-years of the editors and contributors meeting face-to-face at annual American Academy of Religions gatherings, which were structured around the goal of providing “a new turn to ontology” (1). This turn centers upon “how our ideas materialize in the world and how our entanglement with other bodies in an evolving planetary community shape our ideas [and] have great potential for rethinking human-technology-animal-Earth relationships” (1). The editors explain that during this gestation period they discussed the themes of Earthly Things and workshopped ideas and drafts that eventually became the respective contributions from those involved (three editors, nineteen other contributors). Overall, the book is structured around three “main, intersecting themes: Immanent Religiosities, New Materialisms and other theories of Immanence, and Planetary Thinking” (2-3).